An exploratory study of the relationships between advertising appeals, spending tendency, perceived social status and materialism on perfume purchasing behavior - Chan, Benjamin Yin Fah; Yeoh, Sok Foon; Osman, Syuhaily (Center for Promoting Ideas, 2011)
The purpose of the study was to investigate the purchasing behavior of Malaysians and its association with advertising appeals, tendency to spend, perceived social status and materialism. Data for this study was obtained through self-administered using convenience sampling. A total of 120 respondents were collected in Berjaya Megamall Kuantan, Pahang, Malaysia. The findings of the study revealed that those respondents who willing to spend money on perfume product had high level of advertising appeals, perceive social status, materialism and moderate level of tendency to spend. This study is important to the marketers to understand the consumer’s purchasing behavior on perfume. The marketer also could understand the market segmentation than make them to be more competitive and utilize target market wisely.